THE PROSPECT OF PALEKBANG BRIDGE: A DRIVE FOR INCLUSIVE AND EQUITABLE GROWTH IN KELANTAN - MHD RUSLAN, SITI MARSILA; MOKHTAR, KASYPI; RAZAK, RUSLAN (Journal of Maritime Logistics, 2022)
The East Coast Economic Region (ECER) was established in 2007 with the announcement of the ECER Master Plan by the Malaysian Government. Meanwhile, the ECER Development Council (ECERDC) is driving development in the ECER by launching several high-impact projects and programmes to promote socioeconomic transformation by increasing private investment in the region. The ultimate goal is to close the socioeconomic gap between East and West Coasts by empowering local communities to benefit from job and entrepreneurial opportunities. One of the ECER projects is the construction of the Palekbang Bridge in Kelantan, which will connect Kota Bharu and Palekbang, Tumpat. The bridge construction is critical in light of two factors: Congestion at the Sultan Yahya Petra Bridge and limited growth in the Kota Bharu city centre. This paper discusses the role of ECERDC as the primary monitoring body for the project, as well as the potential of the Palekbang Bridge to provide physical, economic, and social benefits to citizens. It is hoped that the bridge construction will address congestion and limited growth, stimulate trade activities, improve connectivity, and accessibility. As a result, economic growth across all economic sectors will be boosted in the coming years.